The Role of Fairness in Wage Determination - Rees, Albert (Journal of Labor Economics, 1993)
Neoclassical wage theory is based on the premise that a worker's utility is based on his own wage and his own hours of work, without reference to the wages and hours of others. This article reviews anecdotal evidence that the wages of others are a powerful force in determining worker satisfaction, such that utility goes down when the wages of others go up. The resulting comparisons are a powerful force in determining wage structure, but do not exclude ultimate effect of neoclassical wage determinants.